A preliminary study on the effects of E-Z Mixin® and EquiPlus® extenders supplemented with Edible Bird's Nest on the quality of chilled Arabian stallion semen - Al-Khaldi, Khalid; Yimer, Nurhusien; Al-Bulushi, Samir; Haron, Abd Wahid; Hiew, Mark Wen Han; Babji, Abdul Salam (Brazilian College of Animal Reproduction, 2021)
The aim of this study was to evaluate the effects of adding different concentrations of edible bird's nest (EBN) which is secreted by swiftlet birds (Aerodramus fuciphagus), into EquiPlus® and E-Z Mixin® extenders on the quality of chilled Arabian stallion semen at various storage times (0, 24 and 48 h). Ten ejaculates were collected from five stallions, and diluted using the two extenders containing 0% (control), 0.12%, 0.24% and 0.24% of EBN + seminal plasma (SP). All the diluted semen samples were then cooled and stored at 5 °C, and examined at 0, 24 and 48 h. Sperm kinetic parameters were assessed using computer assisted sperm analysis (CASA) and viability were assessed using Hoechst33342/PI stain. In both extenders, total motility (TM) and progressive motility (PM) were significantly higher at 0.12% and 0.24% compared to 0.24% + SP at 24 and 48 h. At 0.12%, E-Z mixin® treated semen had significantly higher TM and PM than EquiPlus® at 24 and 48 h. At 0.12% and 0.24%, average path velocity (VAP), straight-line velocity (VSL) and curvilinear velocity (VCL) were significantly higher in E-Z mixin® treated semen compared to EquiPlus® at 24 and 48 h. Comparisons between the two extender types at different concentrations of EBN showed no significant difference in lateral head amplitude (ALH), linearity (LIN), straightness (STR), beat cross frequency (BCF) and viability, irrespective of the storage time. The percentage of viable was significantly higher in E-Z mixin® than EquiPlus® at 0 and 48 h in control and 0.12%. Supplementation of the E-Z mixin® extender with 0.12% and 0.24% EBN concentrations in the absence of SP provided better CASA parameters such as TM, PM, VAP, VSL, and VCL at 24 and 48 h storage time. In conclusion, the results of this study indicated that chilled semen from Arabian stallion that was extended using E-Z mixin® and supplemented with 0.12% and 0.24% EBN concentrations performed better and yielded superior results in sperm kinetic parameters and % viable compared to EquiPlus® at 24 and 48 h storage time.